A Longitudinal Study of the Mini‐Mental State Examination in Late Nonagenarians and Its Relationship with Dementia, Mortality, and Education. Issue 6 (21st March 2017) - Skoog, Johan; Backman, Kristoffer; Ribbe, Mats; Falk, Hanna; Gudmundsson, Pia; Thorvaldsson, Valgeir; Borjesson‐Hanson, Anne; Ostling, Svante; Johansson, Boo; Skoog, Ingmar
Abstract : Objectives: To examine level of and change in cognitive status using the Mini‐Mental State Examination (MMSE) in relation to dementia, mortality, education, and sex in late nonagenarians. Design: Three‐year longitudinal study with examinations at ages 97, 99, and 100. Setting: Trained psychiatric research nurses examined participants at their place of living. Participants: A representative population‐based sample of 97‐year‐old Swedes (N = 591; 107 men, 484 women) living in Gothenburg, Sweden. Measurements: A Swedish version of the MMSE was used to measure cognitive status. Geriatric psychiatrists diagnosed dementia according to the Diagnostic and Statistical Manual of Mental Disorders, Third Edition, Revised. Mixed models were fitted to the data to model the longitudinal relationship between MMSE score and explanatory variables. Results: Individuals with dementia between age 97 and 100 had lower mean MMSE scores than those without dementia. Those who died during the 3‐year follow‐up had lower MMSE scores than those who survived. MMSE scores at baseline did not differ between those without dementia and those who developed dementia during the 3‐year follow‐up. Participants with more education had higher MMSE scores, but there was no association between education and linear change. Conclusion: MMSE score is associated with dementia and subsequent mortality even in very old individuals, although the preclinical phase of dementia may be short in older age. Level of education is positively associated with MMSE score but not rate of decline in individuals approaching age 100.